Binomial coefficient: Additive recursion

Dependencies:

  1. Binomial Coefficient

For $n \ge 1$, \[ \binom{n}{k} = \binom{n-1}{k} + \binom{n-1}{k-1} \]

On rearranging terms and replacing $n$ by $n+1$, we get \[ \binom{n}{k} = \binom{n+1}{k} - \binom{n}{k-1} \] On rearranging terms and replacing $n$ by $n+1$ and $k$ by $k+1$, we get \[ \binom{n}{k} = \binom{n+1}{k+1} - \binom{n}{k+1} \]

Combinatorial proof

When $k < 0$ or $k > n$, all 3 terms are 0, so the identity holds. For $k = 0$, $\binom{n}{k} = 1$ and $\binom{n-1}{k} + \binom{n-1}{k-1} = 1 + 0 = 1$.

For the case when $1 \le k \le n$, we have a combinatorial proof. Suppose we have a set $S$ of $n$ distinct elements. Let $a \in S$.

Therefore, $\binom{n}{k} = \binom{n-1}{k} + \binom{n-1}{k-1}$.

Alternative proof outline

An algebraic proof is also possible by using the decrement identities to express $\binom{n-1}{k}$ and $\binom{n-1}{k-1}$ in terms of $\binom{n}{k}$.

Dependency for:

  1. Algorithm for enumerating tuples with bounded sum
  2. Binomial coefficient: Sum 3
  3. Binomial coefficient: Sum 2
  4. Binomial coefficient: Sum 4

Info:

Transitive dependencies:

  1. Binomial Coefficient